„Somas sar diliňi savorestar, so pregejľom“ / „Z toho všeho, čím jsem si prošla,ocitla jsem se na pokraji svých sil“ - Ferková, Ilona (Romano džaniben, 2025)
Ilona Ferková’s short story sheds light on the issue of domestic violence, which a young Romani woman had to endure at the hands of her husband. Through a vivid narrative rich in dialogue, we learn about the adverse conditions in her husband’s family—even as a child, he witnessed domestic violence against his mother when his father returned home intoxicated. He then behaves just as aggressively toward his wife, and it even escalates to a serious violent attack in which he severely scars her face.